1999
DOI: 10.3758/bf03211559
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity and recollection in item and associative recognition

Abstract: Recognition memory for item information (single words) and associative information (word pairs) was tested immediately and after retention intervals of 30 min and 1 day (Experiment 1) and 2 days and 7 days (Experiment 2) using Tulvmg's (1985) remember/lmow response procedure. Associative recognition decisions were accompanied by more "remember" responses and less "know" responses than item recognition decisions. Overall recognition performance and the proportion of remember responses declined at similar rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
166
3
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(190 citation statements)
references
References 59 publications
18
166
3
3
Order By: Relevance
“…A recent study by Westerman (2001) offers some support for such an interpretation. Using the same priming technique as that used in the present experiment, Westerman (Experiment 1) found that enhanced fluency did not affect associative recognition, a task that is theorized to be largely dependent on recollection (e.g., Clark, 1992;Hockley & Consoli, 1999;Yonelinas, 1997). Given that the fluency heuristic is not used on recognition tests that are based largely on recollection, it is possible that the null effect of the prime that occurred when pictures were studied is the result of a greater reliance on recollection for the group that studied pictures.…”
Section: Resultsmentioning
confidence: 87%
“…A recent study by Westerman (2001) offers some support for such an interpretation. Using the same priming technique as that used in the present experiment, Westerman (Experiment 1) found that enhanced fluency did not affect associative recognition, a task that is theorized to be largely dependent on recollection (e.g., Clark, 1992;Hockley & Consoli, 1999;Yonelinas, 1997). Given that the fluency heuristic is not used on recognition tests that are based largely on recollection, it is possible that the null effect of the prime that occurred when pictures were studied is the result of a greater reliance on recollection for the group that studied pictures.…”
Section: Resultsmentioning
confidence: 87%
“…It is also possible, however, that it reflects a disproportionate deficit in recollection relative to familiarity, since associative recognition is based on conscious recollection to a greater extent than is item recognition,and, conversely, that item memory is based on familiarity to a greater extent than is associative recognition (Hockley & Consoli, 1999). Other studies, however, have demonstrated deficits in relational memory processing that cannot be accounted for by the recollection/ familiarity distinction (Chun & Phelps, 1999;Ryan, Althoff, Whitlow, & Cohen, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…13 Over the last two decades, a number of cognitive studies in young adults have provided empirical evidence for the distinction between item and relational memory. [14][15][16][17] Of relevance here, several recent reports suggest that persons with a diagnosis of MCI show a disproportionate decrease in relational memory, 18,19 and that the relational memory deficits in this group can be predictive of future cognitive impairment. 20,21 The current study was the first to examine whether dissociations between item and relational memory might exist in persons with multiple sport-related concussions.…”
Section: Introductionmentioning
confidence: 85%